Evaluation of two service quality dimensions and customer satisfaction in Ikom hotels, Cross River State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The aim of this study was to assess hotel service quality and customer’s satisfaction in Ikom town, using assurance and empathy dimensions. The specific objectives were to (i) examine the effect of assurance dimension of hotel service quality on customer satisfaction in Ikom (ii) assess the effect of empathy dimension of hotel service quality on customer satisfaction in Ikom and (iii) determine the overall effect assurance and empathy on customers’ satisfaction in Ikom hotels. 296 hotel customers were randomly sampled across ten 2 star hotels in Ikom town. Data were analyze using descriptive and inferential statistics. The result of regression analysis shows that assurance dimension of hotel service quality has significant effect on customers’ satisfaction (76.347; p > 0.05). Empathy was also found to have significant effect on the satisfaction of customers (549.284, p< 0.05). It was concluded that hotel should continue to maintain their services standard to keep their customers and woo more to patronize them.
Keywords: Service quality; customer satisfaction; hotel industry; assurance; empathy